(untitled) (Journal of NELTA, 2011)
Fluency-first approaches such as Communicative Language Teaching and Task-based Language Teaching aim at the development of communicative competence in students by engaging them in meaningful interaction. Ability to speak accurate, appropriate and effective English is vital for meaningful interaction that ensures students’ communicative competence in English. Unfortunately, in the Nepalese context, especially in government-aided schools and constituent colleges of Tribhuvan University (TU), speaking skill lies on the periphery of English Language Teaching (ELT) owing to several factors. This article attempts to explore those factors that have been a hindrance in developing speaking skill in Nepalese students in general and the students from the above-mentioned institutions in particular. This article draws on the author’s experience as a supervisor of student teachers from B.Ed. and M.Ed. programmes and his teaching experience at a constituent campus of TU. Moreover, the article presents some suggestions that can help English teachers to overcome the hindrances. Key words: Speaking skill; Interaction; Teacher-fronted teaching; Learner-centered activities Journal of NELTA Vol. 15 No. 1-2 December 2010 Page: 1-9 Uploaded date: 3 May, 2011 DOI: 10.3126/nelta.v15i1-2.4602